PENERAPAN PENDIDIKAN KARAKTER ANAK USIA DINI DI LINGKUNGAN KELUARGA MELALUI KERJASAMA ORANGTUA DAN GURU DI PAUD AL-MUTADARISIN - Neng Eva Vauziah; Rohmalina Rohmalina (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2020)
Character education an educator who teaches a process story moral behavior and personality. The family was a major role in developing character education for the son of his daughter. In the context of PAUD young kids very well in a stimulus on strengthening character education. Backgrounds encourage research on the importance of strengthening character education for early childhood in the family environment through cooperation between parents and teachers. The problems in the lift in this research aim to improve strengthening character education young kids in the family environment through cooperation parents and teachers in PAUD Al-Mutadarisin. This research in research deskriftif qualitative thought data collection with observation interview documentation and withdrawal o conclusion. The conclusion from the study there is some changes in School tuition afterward applied to strengthen character education in the neighborhood of household through daily activities participants. A character who is more apparent in school tuition namely independence discipline religious and operationCharacter education an educator who teaches a process story moral behavior and personality. The family was a major role in developing character education for the son of his daughter. In the context of PAUD young kids very well in a stimulus on strengthening character education. Backgrounds encourage research on the importance of strengthening character education for early childhood in the family environment through cooperation between parents and teachers. The problems in the lift in this research aim to improve strengthening character education young kids in the family environment through cooperation parents and teachers in PAUD Al-Mutadarisin. This research in research deskriftif qualitative thought data collection with observation interview documentation and withdrawal o conclusion. The conclusion from the study there is some changes in School tuition afterward applied to strengthen character education in the neighborhood of household through daily activities participants. A character who is more apparent in school tuition namely independence discipline religious and operation